Jazz Planet - Atkins, E. Taylor (Everett Taylor), 1967- (Book collections on Project MUSE., 2003)
Music history -- Jazz --> Jazz is typically characterized as a uniquely American form of artistic expression, and narratives of its history are almost always set within the United States. Yet, from its inception, this art form exploded beyond national borders, becoming one of the first modern examples of a global music sensation. Jazz Planet collects essays that concentrate for the first time on jazz created outside the United States. What happened when this phenomenon met with indigenous musical practices? What debates on cultural integrity did this "American" styling provoke in far-flu.